2021
DOI: 10.7150/thno.61677
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three tumor antigens and immune subtypes for mRNA vaccine development in diffuse glioma

Abstract: Rationale: Diffuse glioma patients have high mortality and recurrence despite multimodal therapies. This study aims to identify the potential tumor antigens for mRNA vaccines and subtypes suitable for the immunotherapy of patients with diffuse glioma. Methods: Gene expression profiles and corresponding clinical information were obtained from the Chinese Glioma Genome Atlas (CGGA) and the Cancer Genome Atlas (TCGA) databases. Genetic alterations were extracted from cBioPortal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…2.2 | Identification of core genes related to SV, CO, sepsis score, and group in the weighted co-expression network WGCNA is generally used to identify modules and candidate marker genes related to external sample traits and has been successfully performed in various biological entities, such as cancer and mouse genome. 21,22 Here in this study, WGCNA was applied to quest genes related with biometric, plasma and echocardiographic parameters of septic mice (see Section 5 for details), in an effort to identify core candidate targets by structuring a scale-free gene co-expression network.…”
Section: Rna-seq Profile and Identification Of Differentially Express...mentioning
confidence: 99%
“…2.2 | Identification of core genes related to SV, CO, sepsis score, and group in the weighted co-expression network WGCNA is generally used to identify modules and candidate marker genes related to external sample traits and has been successfully performed in various biological entities, such as cancer and mouse genome. 21,22 Here in this study, WGCNA was applied to quest genes related with biometric, plasma and echocardiographic parameters of septic mice (see Section 5 for details), in an effort to identify core candidate targets by structuring a scale-free gene co-expression network.…”
Section: Rna-seq Profile and Identification Of Differentially Express...mentioning
confidence: 99%
“…We speculated that this may be due to the different EGFR mutation landscapes between the 2 groups (see Figure 6I,6J). Thus, the treatment of LUSC should focus on the CPA3 [ 20] ZNF716 [ 24] FBXW7 [ 25] SAGE1 [27] ARID1A [ 29] RASA1 [ 30] SLCO1B1 [ 32] RB1 [ 35] NF1 [ 43] KEAP1 [ 48] PTEN [ 51] PTEN [ 51] KEAP1 [ 48] NF1 [ 43] RB1 [ 35] SLCO1B1 [ 32] RASA1 [ 30] ARID1A [ 29] SAGE1 [27] FBXW7 [ 25] ZNF716 [ 24] CPA3 [ 20] CUL3 [ 19] Altered in 477 (97.15%) of 491 samples.…”
Section: Wgcnamentioning
confidence: 99%
“…In recent years, with the rapid development of HTS technology, IR has been widely used in disease‐related research. 17 , 18 , 19 , 20 , 21 , 22 , 23 One study found that there were differences in the use of V and J genes in both ÎČ and IGH chains in patients with non‐small cell lung cancer (NSCLC). It was found that the clonality and diversity of the TCR repertoire in the early recurrence patients were increased and decreased, respectively, compared to the early non‐recurrence patients.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In recent years, with the rapid development of HTS technology, IR has been widely used in disease-related research. [17][18][19][20][21][22][23] One study found that there were differences in the use of V and J genes in both ÎČ and IGH chains in patients with non-small cell lung cancer (NSCLC).…”
mentioning
confidence: 99%
See 1 more Smart Citation